The application of δ13C, TOC and C/N geochemistry of mangrove sediments to reconstruct Holocene paleoenvironments and relative sea levels, Puerto Rico - Kendrick, Chris (2019)
We assessed the use of δ13C, TOC and C/N values of bulk sedimentary organic matter (OM) to reconstruct paleoenvironmental and relative sea-level change from mangrove environments in Puerto Rico. The modern distribution of δ13C, TOC and C/N values was described from 63 vegetation and 59 surface sediment samples collected from three sites containing basin and riverine mangrove stands, and was compared to microfossil (foraminiferal and thecamoebian) assemblages. Four vertically-zoned environments were identified: tidal flat (δ13C: −18.6 ± 2.8‰; TOC: 10.2 ± 5.7%; C/N: 12.7 ± 3.1), mangrove (δ13C: −26.4 ± 1.0‰; TOC: 33.9 ± 13.4%; C/N: 24.3 ± 6.2), brackish transition (δ13C: −28.8 ± 0.7‰; TOC: 40.8 ± 11.7%; C/N: 21.7 ± 3.7), and freshwater swamp (δ13C: −28.4 ± 0.4‰; TOC: 42.8 ± 4.8%; C/N: 17.0 ± 1.1). These environments had distinct δ13C, TOC and C/N values, with the exception of the brackish transition and freshwater swamp zones that were difficult to distinguish on a geochemical basis alone. The foraminiferal assemblages were complicated by a group that did not show a relationship to elevation due to the presence of calcareous foraminifera occurring above mean higher high water (MHHW), likely resulting from washover or transport by storms. However, the ratio of foraminifera to thecamoebians (F/T) along with δ13C, TOC and C/N values refines the distinction between brackish and freshwater environments. Using linear discriminant analysis, we applied the δ13C, TOC, C/N and F/T distributions to a 1.7 m core containing a continuous sequence of Rhizophora mangle peat, which began accumulating at ~1650–1930 CE. Together, microfossils, δ13C, TOC, and C/N values, and the core chronology from 137Cs and radiocarbon dating revealed that sediments in the core likely accumulated in response to anthropogenic sediment delivery, making it unsuitable for relative sea-level reconstruction. We caution that in the absence of detailed litho-, bio-, chemo-, or chrono-stratigraphic analyses as presented here, care should be taken in interpreting sea-level histories derived from single dates on mangrove peats.